Libraries, translations, and 'canonic' texts : the Septuagint, Aquila, and Ben Sira in the Jewish and Christian traditions - Veltri, Giuseppe (Supplements to the Journal for the study of Judaism, 2006)
The book deals with the field of decanonization of ancient traditions by the technique of deconstructing their original context; in particular: the process of canonization of the Greek Torah in Jewish-Hellenistic and Christian tradition and its decanonization in Rabbinic literature; the use and abuse of the translation(s) of Aquila in Patristic and Rabbinic literature and the substitution of Aquila by Onkelos in Babylonian academies; the decanonization of the book of Ben Sira in Rabbinic literature. On the basis of his analysis, the author concludes that, if a canon is the ability of a text to produce and authorize commentary deconstructing its original context by generalization, de-canonization is the inverse way of contextualizing a 'canonical' text by reconstructing the supposed original context.